Beyond the gene : cytoplasmic inheritance and the struggle for authority in genetics - Sapp, Jan (Oxford University Press, 1987)
The scope and significance of cytoplasmic inheritance has been the subject of one of the longest controversies in the history of genetics.In the first major book on the history of this subject, Jan Sapp analyses the persistent attempts of investigators of non-Mendelian inheritance to establish their claims in the face of strong resistance from.